Continuous bubble reactor using carbon dioxide and its mixtures for ballast water treatment. (1st May 2019) - Baek, Jun-Tae; Hong, Jae-Hoon; Tayyab, Muhammad; Kim, Doo-Wook; Jeon, Pil Rip; Lee, Chang-Ha
Abstract: The treatment of ballast water is indispensable for preventing ecological and economic damage from the spread of invasive species. In this study, a continuous gas bubble reactor (CBR) system was developed for the efficient disinfection of microorganisms in ballast water. Ballast water treatment (BWT) in the CBR was experimentally performed to disinfect Artemia salina in seawater by using 1) pure CO2 and 2) mixtures with CO2, N2, and/or SO2 as a simulated flue gas (CO2 /N2 : 20%/80% and CO2 /N2 /SO2 : 19.2%/77.0%/3.8%). The BWT efficiency was improved with an increase in gas flowrate, residence time, gas pressure, and CO2 concentration in the gas. The toxicity of SO2 in the CO2 mixture significantly improved the mortality of microorganisms. Since good dispersion of bubbles and effective contact between bubbles and liquid were important factors in the BWT, a 100% mortality rate of microorganisms could be achieved by controlling the operating conditions in the vertical-type CBR with a counter-current flow between the gas bubbles and seawater. The CO2 gas distribution, CO2 solubility, and gas bubble size distribution in the CBR were determined using computational fluid dynamics (CFD) and experimentally confirmed using a high-speed camera. Since excess gas can be recovered from a gas-liquid separator before a ballast tank, the CBR system can be operated without using any toxic or explosive gases in an eco-friendly and energy saving manner. Graphical abstract: Image 1 Highlights: Bubble reactor using CO2 was developed for ballast water disinfection. Physical and chemical effects of CO2 on microorganisms led to high mortality. SO2 in ship flue gas had a critical effect on the disinfection of microorganisms. High performance was achieved with high safety and low energy consumption.